Red Beard - Yamamoto, Shūgorō 1903-1967; Satō, Masaru 1928-1999; Yamamoto, Shūgorō 1903-1967 (<<The>> Criterion Coll., 2002)
A vain young doctor learns a valuable lesson from the dedicated director of a clinic for destitute patients.
Bildformat 2.35:1 (16:9) - New, restored high-definition digital transfer, with restored image and sound and enhanced for widescreen televisions
Orig.: Japan 1965
Enth. audio commentary by Kurosawa film scholar Stephen Prince ; notes by Japanese-film historian Donald Richie
Keywords: Ishi - Nihon - Dorama; Medizin; Japanese language materials; Medicine -- Japan -- Drama; Japan -- Social conditions -- 1600-1868 -- Drama; Feature films; Foreign films - Japan; Motion pictures, Japanese